PENGARUH IKLAN GOOGLE ADS TERHADAP BRAND AWARENESS PADA PT. JASA TITIPAN EKPRES JAKARTA - Faisal H Batubara; chairul hadi; Yudani Gambiro (Politeknik APP Jakarta, 2022)
ABSTRACTThis study aims to determine the application of Google Ads at PT. Jasa Titipan Ekspres and to find out whether there is an effect of Google Ads advertising on Brand Awareness at PT. Jasa Titipan Ekspres. The analysis used is descriptive quantitative analysis with a sample of 50 respondents with purposive sampling technique with criteria, is a customer of PT. Jasa Titipan Ekspres and have seen google ads. The analysis technique used is validity test, reliability test, simple regression analysis, correlation coefficient test, coefficient of determination test, and T test. the brand awareness variable of 0.639 means that every one increase in the value of Google Ads Ads will be followed by 0.639 the value of Brand Awareness. Then based on the correlation coefficient test, it is known that the R value of 0.521 means that Google Ads Ads (X) has a 'medium' relationship to Brand Awareness (Y) at PT. Jasa Titipan Ekspres. Then based on the coefficient of determination R2 the independent variable (Google Ads) has an influence on the dependent variable (Brand Awareness) of 27.1% while the rest is influenced by other variables and based on the T test it can be concluded that t count > t table (4.224 > 1.299) which means that there is a significant influence between Google Ads Ads on Brand Awareness of PT. Jasa Titipan Ekspres and there is a close influence between Google Ads Ads on Brand Awareness of PT. Jasa Titipan Ekspres.Keywords: Google Ads Advertising, Brand Awareness, PT. Express Delivery Service ABSTRAKPenelitian ini bertujuan untuk mengetahui penerapan Google Ads di PT. Jasa Titipan Ekpres dan untuk mengetahui apakah ada pengaruh iklan Google Ads terhadap Brand Awareness pada PT. Jasa Titipan Ekpres. Analisis yang digunakan adalah analisis deskriptif kuantitatif dengan sampel 50 responden dengan teknik purposive sampling dengan kriteria, merupakan customer PT. Jasa Titipan Ekpres dan pernah melihat iklan google ads. Teknik analisis yang digunakan adalah uji validitas, uji reliabilitas, analisis regresi sederhana, uji koefisien korelasi, uji koefisiensi determinasi, dan uji T. Berdasarkan analisis data yang telah diperoleh, berdasarkan uji regresi sederhana diperoleh hasil Y= 190,165+ 0,639X yang artinya koefisiensi regresi variabel brand awareness sebesar 0,639 artinya setiap peningkatan satu nilai Iklan Google Ads akan diikuti oleh 0,639 nilai Brand Awareness. Lalu berdasarkan uji koefisiensi korelasi diketahui bahwa nilai R sebesar 0,521 artinya Iklan Google Ads (X) memiliki hubungan ‘sedang' terhadap Brand Awareness (Y) pada PT. Jasa Titipan Ekpres. Lalu berdasarkan uji koefisiensi determinasi R2 variabel independen (Iklan Google Ads) memiliki pengaruh terhadap variabel dependen (Brand Awareness). Kata Kunci : Iklan Google Ads, Brand Awareness, PT. Jasa Titipan Ekspres